The overconfidence bias in identification and recognition tasks of gustative stimuli - Razumiejczyk, Eugenia (2009)
The psychology of thinking has defined calibration as the relation of convergence or divergence between the objective success or actual performance and the subjective success or personal estimation of achievement. The most observed calibration phenomena known as overconfidence bias is defined as the predominance of the subjetive success over the objective success. This calibration bias has been studied in several tasks. The aim of the present study is to extend the state of the art on overconfidence bias in the direction of taste perception. An experiment was conducted to generate this distortion in tasks of identification and recognition of gustative stimuli. Results are consistent with previous studies and generalize the overconfidence bias to the gustative modality.